A Novel, Five-Marker Alternative to CD16–CD14 Gating to Identify the Three Human Monocyte Subsets - Ong, Siew-Min; Teng, Karen; Newell, Evan; Chen, Hao; Chen, Jinmiao; Loy, Thomas; Yeo, Tsin-Wen; Fink, Katja; Wong, Siew-Cheng (Frontiers in Immunology, 2019)
Human primary monocytes are heterogeneous in terms of phenotype and function, but are sub-divided only based on CD16 and CD14 expression. CD16 expression distinguishes a subset of monocytes with highly pro-inflammatory properties from non-CD16 expressing “classical” monocytes. CD14 expression further subdivides the CD16+ monocytes into non-classical CD14low and intermediate CD14high subsets. This long-standing CD16–CD14 classification system, however, has limitations as CD14 is expressed in a continuum, leading to subjectivity in delineating the non-classical and intermediate subsets; in addition, CD16 expression is unstable, making identification of the subsets impossible after in vitro culture or during inflammatory conditions in vivo. Hence, we aimed to identify the three monocyte subsets using an alternative combination of markers. Additionally, we wanted to address whether the monocyte subset perturbations observed during infection is real or an artefact of differential CD16 and/or CD14 regulation. Using cytometry by time-of-flight (CyTOF), we studied the simultaneous expression of 34 monocyte markers on total monocytes, and derived a combination of five markers (CD33, CD86, CD64, HLA-DR and CCR2), that could objectively delineate the three subsets. Using these markers, we could also distinguish CD16+ monocytes from CD16- monocytes after in vitro stimulation. Finally, we found that the observed expansion of intermediate (CD14high) monocytes in dengue virus-infected patients was due to up-regulated CD16 expression on classical monocytes. With our new combination of markers, we can now identify monocyte subsets without CD16 and CD14, and accurately re-examine monocyte subset perturbations in diseases.